Tree Improvement in Canada – past, present and future, 2023 and beyond - Barb R. Thomas; Michael Stoehr; Stefan G. Schreiber; Andy Benowicz; William R. Schroeder; Raju Soolanayakanahally; Chris Stefner; Ken A. Elliott; Newton Philis; Ngaire Roubal; Pierre Périnet; Martin Perron; et al. (The Forestry Chronicle)
This paper consolidates the most current information available on tree improvement in Canada and provides a summary of key historical events leading to its development and expansion across the country. The most recent publication on the topic was by Fowler and Morgenstern (1990) compiled over 30 years ago. Since that time, many things have changed and new technologies, such as the increasing use and adoption of genomics, have become part of the tool-box of tree breeders in forestry and natural resource management. This paper provides information on the status of tree improvement programs including their history, objectives, seed production, future outlook and other performance measures by province across Canada.